2021
DOI: 10.1016/j.ijid.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance: A challenge awaiting the post-COVID-19 era

Abstract: Microbe exposure to pharmaceutical and non-pharmaceutical agents plays a role in the development of antibiotic resistance. The risks and consequences associated with extensive disinfectant use during the COVID-19 pandemic remain unclear. Some disinfectants, like sanitizers, contain genotoxic chemicals that damage microbial DNA, like phenol and hydrogen peroxide. This damage activates error-prone DNA repair enzymes, which can lead to mutations that induce antimicrobial resistance. Public health priority program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
0
35
0
4
Order By: Relevance
“…It has been recently demonstrated that human contact restrictions and other strategies to prevent SARS-CoV-2 transmission during the COVID-19 pandemic have limited the spread of K. pneumoniae and other ESKAPE pathogens [ 87 , 88 ]. However, the extensive use of disinfectants and increased administration of antibiotics to prevent bacterial co-infections during the COVID-19 pandemic may enhance the emergence and spread of drug resistance [ 89 , 90 , 91 ]. Several studies have indicated that the prevalence of carbapenem-resistant K. pneumoniae co-infection in COVID-19 patients may reach more than 50% of cases [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently demonstrated that human contact restrictions and other strategies to prevent SARS-CoV-2 transmission during the COVID-19 pandemic have limited the spread of K. pneumoniae and other ESKAPE pathogens [ 87 , 88 ]. However, the extensive use of disinfectants and increased administration of antibiotics to prevent bacterial co-infections during the COVID-19 pandemic may enhance the emergence and spread of drug resistance [ 89 , 90 , 91 ]. Several studies have indicated that the prevalence of carbapenem-resistant K. pneumoniae co-infection in COVID-19 patients may reach more than 50% of cases [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high antibiotic utilization may have contributed to the increase in MDRGNs among COVID-19 patients, together with other factors (altered infection control practices, critical illness and prolonged hospital stay of COVID-19 patients) [ 114 ]. Ukuhor (2021) reported that various types of bacterial and fungal infections occur in patients with COVID-19 with some resistant to antimicrobials that are associated with significantly worse outcomes and deaths [ 115 ]. In another study of Lobie et al (2021) [ 115 ] is reported that some disinfectants, such as sanitizers, contain genotoxic chemicals that damage microbial DNA, activating error-prone DNA repair enzymes, which can lead to mutations that induce antimicrobial resistance.…”
Section: Mdr and Antiviralsmentioning
confidence: 99%
“…Ukuhor (2021) reported that various types of bacterial and fungal infections occur in patients with COVID-19 with some resistant to antimicrobials that are associated with significantly worse outcomes and deaths [ 115 ]. In another study of Lobie et al (2021) [ 115 ] is reported that some disinfectants, such as sanitizers, contain genotoxic chemicals that damage microbial DNA, activating error-prone DNA repair enzymes, which can lead to mutations that induce antimicrobial resistance. On the other hand, it is fair to report a retrospective study that demonstrated a reduction in MDR bacterial infections during the COVID-19 pandemic.…”
Section: Mdr and Antiviralsmentioning
confidence: 99%
“…Antimicrobial-resistant (AMR) bacterial infections pose an emerging health problem globally, with a disproportionate impact in low and middle-income countries (LMICs) [ 1 , 2 ]. The COVID-19 pandemic has potentially escalated this problem due to increased use of antibiotics in patients hospitalized with COVID-19 [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%